Analysis of dietary patterns on the nutritional status of pregnant women in Depok City, West Java - Arlym, Lisa Trina; Rukmaini, Rukmaini; Mahmudah, Enok Siti R (Alma Ata University Press, 2025)
Background: The nutritional status of pregnant women affects fetal growth. Inadequate nutrition intake can lead to poor maternal nutritional status, ultimately resulting in insufficient nutrients being transferred to the fetus. A good and correct dietary pattern and nutritional intake will meet the nutritional needs of pregnant women. Objectives: To determine the relationship between dietary pattern and nutritional intake with the nutritional status of pregnant women, including CED status, anemia status and weight gain in Pancoran mas, Depok City . Methods: This study was a prospective cohort conducted on 115 pregnant women. Respondents were observed for 7 days over 4 weeks to measure their dietary patterns and nutritional intake using Food Frequency Questionnare (FFQ) and the 24-hour Food Record and then processed using Nutrisurvey. Their nutritional status was then measured. CED and anemia status were measured using MUAC and hemoglobin tester after observation. Weight gain was measured before and after observation. The data were analyzed using the chi-square test. Results: The average energy intake of respondents was 1.884,2 ± 383,30 kcal/day; the average protein intake was 79 ± 14,75 gram/day; the average iron intake was 24,8 ± 12,3 mg/day; and the average folic acid intake was 359,6 ± 83,04 mcg/day. There was a relationship between dietary patterns and the risk of CED, anemia status, and weight gain (p<0.05). There was a relationship between energy and protein intake and weight gain in pregnant women (p<0.05).Conclusions: Dietary patterns are related to the nutritional status of pregnant women. The average intake of energy, protein, iron, and folic acid in pregnant women is still far from the nutritional adequacy level. Health workers are expected to strengthen nutrition education, and pregnant women are expected to pay attention to their dietary patterns and nutritional intake during pregnancy.